Labral Reattachment in Femoroacetabular Impingement Surgery Results in Increased 10‐year Survivorship Compared With Resection. Issue 4 (April 2017) - Anwander, Helen; Siebenrock, Klaus A.; Tannast, Moritz; Steppacher, Simon D.
Abstract: Background: Since the importance of an intact labrum for normal hip function has been shown, labral reattachment has become the standard method for open or arthroscopic treatment of hips with femoroacetabular impingement (FAI). However, no long‐term clinical results exist evaluating the effect of labral reattachment. A 2‐year followup comparing open surgical treatment of FAI with labral resection versus reattachment was previously performed at our clinic. The goal of this study was to report a concise followup of these patients at a minimum of 10 years. Questions/purposes: We asked if patients undergoing surgical hip dislocation for the treatment of mixed‐type FAI with labral reattachment compared with labral resection had (1) improved hip pain and function based on the Merle d'Aubigné‐Postel score; and (2) improved survival at 10‐year followup. Methods: Between June 1999 and July 2002, we performed surgical hip dislocation with femoral neck osteoplasty and acetabular rim trimming in 52 patients (60 hips) with mixed‐type FAI. In the first 20 patients (25 hips) until June 2001, a torn labrum or a detached labrum in the area of acetabular rim resection was resected. In the next 32 patients (35 hips), reattachment of the labrum was performed. The same indications were used to perform both procedures during the periods in question. Of the 20 patients (25 hips) in the first group, 19 patients (95%) (24 hips [96%]) were available for clinical and/or radiographic followup at a minimum of 10 years (mean, 13 years; range, 12‐14 years). Of the 32 patients (35 hips) in the second group, 29 patients (91%) (32 hips [91%]) were available for clinical and/or radiographic followup at a minimum of 10 years (mean, 12 years; range, 10‐13 years). We used the anterior impingement test to assess pain. Function was assessed using the Merle d'Aubigné‐ Postel score and ROM. Survivorship calculation was performed using the method of Kaplan‐Meier with failure defined as conversion to THA, progression of osteoarthritis (of one grade or more on the Tönnis score), and a Merle d'Aubigné‐Postel score < 15. Results: At the 10‐year followup, hip pain in hips with labral reattachment was slightly improved for the postoperative Merle d'Aubigné‐Postel pain subscore (5.0 ± 1.0 [3‐6] versus 3.9 ± 1.7 [0‐6]; p = 0.017). No difference existed for the prevalence of hip pain assessed using the anterior impingement test with the numbers available (resection group 52% [11 of 21 hips] versus reattachment group 27% [eight of 30 hips]; odds ratio, 3.03; 95% confidence interval [CI], 0.93‐9.83; p = 0.062). Function was slightly better in the reattachment group for the overall Merle d'Aubigné‐Postel score (16.7 ± 1.5 [13‐18] versus 15.3 ± 2.4 [9‐18]; p = 0.028) and hip abduction (45° ± 13° [range, 30°‐70°] versus 38° ± 8° [range, 25°‐45°]; p = 0.001). Hips with labral reattachment showed a better survival rate at 10 years than did hips that underwent labral resection (78%; 95% CI, 64%‐92% versus 46%, 95% CI, 26%‐66%; p = 0.009) with the endpoints defined as conversion to THA, progression of osteoarthritis, and a Merle d'Aubigné‐Postel score < 15. With isolated endpoints, survival at 10 years was increased for labral reattachment and the endpoint Merle d'Aubigné score < 15 (83%, 95% CI, 70%‐97% versus 48%, 95% CI, 28%‐69%; p = 0.009) but did not differ for progression of osteoarthritis (83%, 95% CI, 68%‐97% versus 81%, 95% CI, 63%‐98%; p = 0.957) or conversion to THA (94%, 95% CI, 86%‐100% versus 87%, 95% CI, 74%‐100%; p = 0.366). Conclusions: The current results suggest the importance of preserving the labrum and show that resection may put the hip at risk for early deterioration. At 10‐year followup, hips with labral reattachment less frequently had a decreased Merle d'Aubigné score but no effect on progression of osteoarthritis or conversion to THA could be shown. Level of Evidence: Level III, therapeutic study.